Evaluation technology and methodology for improving hammer throwing technique using vertical elastic coupling - Song Haiming (Theory and Practice of Physical Culture, 2025)
Objective of the study. To describe the evaluation technology and methodology of improving the hammer throwing technique using vertical elastic coupling. Methods and structure of the study. Experimental studies were conducted in China on the basis of the sports team of Shaanxi province. We evaluated a number of kinematic parameters of athletes’ movements. Results and conclusions. The use of aids with vertical elastic links has a positive effect on the technical movements of hammer throwers, which is reflected not only in the improvement of hammer movement parameters, its throwing speed and angular velocity of rotation, but also in the improvement of biomechanical parameters and indicators of physical fitness of athletes.